Preparation and characterization of polypropylene/clay nanocomposites - Lim, Jia Jie. (2010)
Polypropylene/clay nanocomposites were synthesized by melt compounding with Cloisite® 20A nanoclay and three different types of compatibilizer in a twin-screw extruder. Different loading of polypropylene maleic alternated polymer (X-10016), polypropylene maleic terminated polymer (X-10088) and polypropylene-graft-maleic anhydride (Commercial) were used as compatibilzer in this study. The purpose is to investigate the effects of different types of compatibilizer on the structure, morphology and properties of polypropylene/clay nanocomposites (PPCNs). The morphology of PPCNs was been characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The XRD patterns and TEM images showed the intercalation of clay layers in polypropylene (PP) matrix of the PPCNs. XRD patterns showed that PP/X-10016/20A hybrids have the highest d-spacing among the three types of PPCNs but the TEM image showed a heterogeneous dispersion of clay. The presence of terminated MAPP, X-10088 resulted in the most uniform clay dispersion. The crystallization behavior of PPCNs was studied by XRD and differential scanning calorimetry (DSC). Characteristic peaks of the PP α-phase crystallites were observed in the XRD graph of the PPCNs. No traces of PP β-phase and γ-phase crystallites are observed. The crystallinity of PP/X-10016/20A hybrids has no changes whereas the crystallinity of PP/X-10018/20A hybrids and PP/Commercial/20A hybrids increases as the MAPP/clay weight ratio increases.